NATO Science Series
DOI: 10.1007/1-4020-3252-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Radionuclides with Humic Substances

Abstract: Humic substances are ubiquitous compounds presenting specific properties with respect to complexation, sorption and transport. Because they may enhance metal solubilities due to their strong complexing properties, as well as increase or decrease metal retention on mineral surfaces due to their affinity for mineral substrates and their scavenging properties, humic substances may impact metal speciation in the environment, and in particular radionuclides speciation. Various examples based on actinides, lanthanid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…At such low pH, the solubility of Al, Th, and U is favoured and the release of a series of elements is expected to increase (Hindar and Nordstrom, 2015;Landa, 2007), whereas scavenging by Fe (oxy)hydroxides will be minimal (Jeng, 1992;Singer and Stumm, 1970). Furthermore, the presence of organic matter can play an important role in changing the speciation, and thus mobility, of elements with high affinity for humic substances, such as Ni, Zn, Cu, Cd, Pb and U (Moulin et al, 2004). Therefore, the weathering of and leaching from alum shale will depend on the storage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At such low pH, the solubility of Al, Th, and U is favoured and the release of a series of elements is expected to increase (Hindar and Nordstrom, 2015;Landa, 2007), whereas scavenging by Fe (oxy)hydroxides will be minimal (Jeng, 1992;Singer and Stumm, 1970). Furthermore, the presence of organic matter can play an important role in changing the speciation, and thus mobility, of elements with high affinity for humic substances, such as Ni, Zn, Cu, Cd, Pb and U (Moulin et al, 2004). Therefore, the weathering of and leaching from alum shale will depend on the storage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The colloid-facilitated transport of actinides has attracted considerable attention following the pioneering work of McCarthy and Zachara . And since then extensive evidence finds for colloid facilitated mobilization of actinides, both in field studies , and in laboratory experiments. ,, On the other hand, a retarded transport of actinides in porous media, such as soils and sediments, has been reported as well. The direct correlations between accumulation of Pu and the content of total organic carbon (TOC) in soils and sediments were observed. , It was also reported that the migration rate of Pu can be reduced substantially with an increase in the soil’s organic content. , …”
Section: Introductionmentioning
confidence: 99%
“…These above cited studies have motivated numerous investigations regarding the impact of humic substances (HS) on actinide transport in aquatic systems and soils. , HS comprise of 50–80% of natural organic matter (NOM), and their molecular structures include reducing and complexing units, which provide for both redox and complexing interactions with plutonium and other actinides. ,, Comparable interactions with plutonium are characteristic of bacterial exopolymers as recently reported in the literature. , Given that these humic materials occur throughout the environment both in mobile colloidal and immobile organo-inorganic states they can be considered as important matricies for manipulating and controlling actinide migration.…”
Section: Introductionmentioning
confidence: 99%